60GHz divider design - Tay, Wei Shi. (2011)
The opening up of the 57GHz - 64GHz un-channelized spectrum for license-free operation in 2001 prompted intensive effort in developing Radio Frequency integrated circuits and systems operating at the Giga-hertz range. Rapid evolution of the low-cost submicrometer CMOS process technology has aided in the development of more compact, lower power, higher speed and wider bandwidth millimeter-wave applications.